Preparation of a water-based antibacterial ink based on microcapsules. Issue 1 (April 2019) - Chen, Haisheng; Li, Na; Pi, Yangxue; Fu, Wenting; Guan, Yanyan
Abstract: In this paper a water-based antibacterial ink with a proper recipe is obtained where antibacterial microcapsules is prepared by β -cyclodextrin embedding cinnamon essential oil, a waterborne acrylate resin is used as a binder and the ethanol and water are the solvents, and followed that pigments, fillers and various additives are added to prepare water-based antibacterial ink for PE film printing. The viscosity, fineness, gloss, initial drying, water resistance and antibacterial properties of the ink are detected successively, and the influence of the addition of antibacterial microcapsules on the performance of the ink is discussed accordingly. The results show that the water-based antibacterial ink possesses the good physical performances in the following fraction of w (waterborne acrylic resin liquid) = 40%, w (ethanol) = 30%, w (water) = 10%, w (carbon black) = 8%, w (adjuvant) = 5%, and w (antimicrobial microcapsules) = 7% (all relative to the total amount of ink). As a result, this ink shows a viscosity of 34.5mPa·s, a fineness of 15μm, a glossiness of 85%, an initial dryness of 15mm/30s, a water resistance of 4 grades and an inhibition zone diameter of 22mm and 14mm for escherichia coli and penicillium, respectively.